NUMERICAL MODEL OF SEDIMENT TRANSPORT DRIVEN BY WAVE INDUCED CURRENT IN PULAU BAAI COASTAL WATERS BENGKULU : Abstract - Setiawan NIM. 224 02 001, Ichsan
Abstract: Numerical model of sediment transport driven by wave induced current has been simulated to investigate a pattern of erosion-sedimentation in Pulau Baai coastal waters Bengkulu. The model used is 2D horizontal, explicit finite difference model. Hydrodynamic model has verified by the Longuet-Higgins analytic model and the Watanabe synthetic model (1986). Comparison of the model with Longuet-Higgins model showed good result with error about 1.9 %, while with Watanabe model is 3.5 %. Sediment transport and hydrodynamics model are simulated for 7 days in east and west monsoon respectively. The result of hydrodynamics model near coast line has shown that current pattern is agree with observed one of PPGL (1996). The simulated current circulation in west monsoon is flowing toward southwest with the speed of 0.15 m/s in southwest part of the port channel and 0.36 m/s in northeast part. In east monsoon the current flow toward northeast with the speed of 0.18 m/s in southwest of the port channel and 0.27 m/s in northeast part. The simulation result of sediment transport model is qualitatively quite comparable with observed data of PPGL (2001). The results in west season have identified erosion area in southwest part of channel while in northeast part dominate by sedimentation. In east season, the model indicate that in southwest part is dominated by sedimentation and northeast part by erosion.